Enhancement of production of Pashmina goats by mineral and nutrient supplementation in Changthang region of Ladakh - SHABIR, MIR; KANWAR, M S; KUBREVI, S S; YATOO, MOHD IQBAL; KUMAR, SANJAY; LASKIT, JIGMET (The Indian Journal of Animal Sciences, 2017)
The present study was designed to determine the effect of mineral and nutrient supplementation on Pashmina production of Changthangi goats and birth weight of their kids in cold arid region of Changthang, Ladakh. Bucks (24) of same age and body weight were selected and divided randomly into four groups of 6 animals each to access pashmina production. Similarly, in 2nd experiment, pregnant does (24) were randomly selected and divided into four groups of 6 animals each to access the birth weight of their kids. The bucks and does were 2 to 3 years of age with average body weight of 40±2.87 kg. Experimental feeding was done for 60 days which was started in December month for both experiments. Each group in both experiments was assigned with four treatments namely T0, T1, T2 and T3. The goats in the control group (T0) were fed with basal ration as per farmers practice, without nutrient and mineral supplementation. The goats of the treatment group (T1) received only mineral supplement (agrimin forte supplement @ 10 g/day) without nutrient supplement in addition to basal ration. The T2 and T3 group received agrimin forte supplement @ 10 g/day with concentrated feed supplement in pellet and mashed form respectively @ 250 g/day. The pashmina production in T0, T1, T2 and T3 groups was recorded to be 221.33±3.33, 244.84±2.26, 247.66±5.58 and 246.0±5.46 g, respectively. In comparison to the control group, all the supplemented groups produced significantly higher pashmina. The birth weight of kids in T0, T1, T2 and T3 groups was 2.85±0.08, 3.08±0.07, 3.39±0.1 and 3.66±0.07 kg, respectively. T3 group showed significantly higher birth weight of kids than the other groups. On the basis of these results, it can be concluded that the supplementation showed a positive effect on pashmina production of bucks as well as on birth weight of kids of supplemented does.